Determining Relevance of Formal Bachelor/Masters Level Marketing Courses for Marketing Professionals in Bangalore with Experience of 0-20 Years - Satpathy, Tridibesh (Digital Repository of Theses, 2023)
It is generally believed that the relevance of most of the formal Marketing programs may be higher for freshers who are joining their initial jobs, but the relevance decreases significantly over time. However, there has been little work done on the relevance of formal marketing programs for marketing professionals in Bangalore. This research is being conducted to explore and understand the relevance of formal marketing degrees for marketing professionals who have 0-20 years of marketing experience in Bangalore. The key objectives of the study are: 1. To identify to what extent marketing professionals consider their formal marketing degrees to be relevant with respect to different aspects of marketing. 2. To determine what additional steps were taken by marketing professionals to bridge the gap between their formal education and knowledge required in be productive in their profession. 3. To determine how marketing professionals perceive the relevance of their marketing degree 20+ years after completing their formal marketing course. The study showed that over time, there is a significant decrease in perceived relevance of formal Bachelors, Masters, or PhD/Doctoral Marketing course, compared with the knowledge required by marketing professionals on the job – and the percentage perceived relevance decreases from 86.12% for marketing professionals with experience of 0-3 years, to 46.21% for marketing professionals with more than 20 years of experience. The study also showed that different aspects of marketing had differing decrease in relevance over time – with the most pronounced decrease in relevance being for Digital Marketing, where the perceived relevance of the formal marketing course, compared with the knowledge required by marketing professionals on the job – decreased from 88% relevance for marketing professionals with experience of 0-3 years to as low as 4% with marketing professionals with more than 20 years of experience. By quantifying the decrease in relevance of marketing education with the egress of time, the research from this study can be used very effectively by marketing professionals, marketing students, corporates employing marketing professionals, and training providers offering marketing courses – to fine-tune and provide appropriate marketing training and courses for marketing professionals. This will help ensure that the education of all marketing professionals is relevant to their actual job roles, and that they can perform effectively and to the best of their abilities. The research is done only for marketing professionals in Bangalore, but may be used for further study in other cities in India and also in other countries. Similar research could also be conducted in other professional fields such as Finance, Human Resources Management, Project Management, Technology, Operations, etc. By identifying the gaps in education over time for professionals in any field, it will be possible to fine-tune the training requirements for such professionals to maximize their performance in their field of expertise.